Developmental Changes in Morphology of the Middle and Posterior External Cranial Base in Modern Homo sapiens. (27th August 2015) - Dalal, Deepal H.; Smith, Heather F.
Abstract : The basicranium has been described as phylogenetically informative, developmentally stable, and minimally affected by external factors and consequently plays an important role in cranial size and shape in subadult humans. Here basicranial variation of subadults from several modern human populations was investigated and the impact of genetic relatedness on basicranial morphological similarities was investigated. Three-dimensional landmark data were digitized from subadult basicrania from seven populations. Published molecular data on short tandem repeats were statistically compared to morphological data from three ontogenetic stages. Basicranial and temporal bone morphology both reflect genetic distances in childhood and adolescence (5–18 years), but not in infancy (<5 years). The occipital bone reflects genetic distances only in adolescence (13–18 years). The sphenoid bone does not reflect genetic distances at any ontogenetic stage but was the most diagnostic region evaluated, resulting in high rates of correct classification among populations. These results suggest that the ontogenetic processes driving basicranial development are complex and cannot be succinctly summarized across populations or basicranial regions. However, the fact that certain regions reflect genetic distances suggests that the morphology of these regions may be useful in reconstructing population history in specimens for which direct DNA evidence is unavailable, such as archaeological sites.